High Order Thinking Skills: Strategies for Raising Student’s Thinking Processes and Children’s Cognitive Development in Reading Comprehension - Reni Anggraeni (Journal of Language Learning and Research (JOLLAR), 2018)
This article presents various strategies for raising student’s high order thinking skills (HOTS) in reading comprehension. Basically, to be able to raise the capability of HOTS, a student is encouraged to have better thinking processes so that varied strategies to implement HOTS will work out properly and accordingly. Just like children’ cognitive development, HOTS is best put into practice since early childhood. The strategies to improve the student’s critical thinking skills in reading comprehension are described thoroughly in three different ways: 1) seven strategies proposed by the National Reading Panel, 2) word reading skills proposed by Mellard et al. (2010), and 3) Vocabulary knowledge proposed by Wise et al. (2007). This article is developed based on the importance of 21st century skills proposed by National Commission on Excellence in Education, Common Core State Standards Initiative, Partnership for 21 Century Skills, and Secretary’s Commission on Achieving Necessary Skills to be included in today’s curriculum. According to the one of the organisations proposing the 21st century skills, students and young generation are demanded to be able to acquire specific soft skills pertaining to critical thinking.